Automatic Mushroom House Monitoring System (MHMS) Using Internet Of Things (IoT) - Muhammad Syafik Ikmal, Nazaruddin (2023)
Malaysia's mushroom industry is experiencing a surge in both domestic and international demand, creating significant expansion opportunities. The Malaysian government supports mushroom cultivation as a high-value commodity, recognizing its potential. The rise in mushroom cultivation areas from 78 hectares in 2010 to 340 hectares in 2020 reflects the increasing demand. To capitalize on this opportunity, an Internet of Things (IoT)-based automatic mushroom house monitoring system (MHMS) is proposed. This project incorporates hardware, such as the DHT22 sensor, Node MCU esp8266 microcontroller, fan, and water pump, to regulate the temperature and humidity within the mushroom house. A relay with dual channels regulates the fan and water pump. The software development process involves the construction of smart mobile applications that monitor the temperature, humidity, and operation of the exhaust and water pumps. With sensors and smartphone applications for real-time monitoring, growers can optimize growing conditions and enhance the cultivation process. The IoT-based environmental monitoring system meets the specific requirements of Malaysia's mushroom industry by monitoring critical climatic factors within mushroom houses. The agile development methodology is utilized because of its rapid capability demonstration and resource efficiency. By regulating temperature and humidity, the system hopes to preserve crop quality and boost efficiency. The mushroom industry in Malaysia has significant growth potential, which can be exploited with government support and the implementation of innovative technology.